Mendesain Skema Penanganan Isu Kesehatan Mental Mahasiswa di Prodi Psikologi Islam IAIN Kediri (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
Mental health issues are an important topic of discussion in all circles. Not a few students face situations that contain higher psychological risks such as depression, emotional problems, irritation, stress, insomnia, and post traumatic symptoms as well as excessive worry, melancholia, decreased appetite, are other symptoms that may develop. Students are also an inseparable part of higher education, their existence cannot be separated from the main element of faculty. There are consisting of leaders of faculty, lecturer, psychology laboratories, HMPS, and peer counselor are important elements that can collaborate to create organizational communication in order to overcome student mental health problems. This research has three main objectives: (1) to explore organizational communication practices currently occurring in the Psychology Faculty at campus X; (2) to explore the response of each element of the Psychology faculty campus X. This research approach used was qualitative with case studies. Data was collected through FGD with all faculty elements with a total of 26 people. The results of the research show that the communication practices downward, upward and horizontally communication, but there is still a need to increase the effectiveness communication, so that any informatioan that develops in Psychology faculty can be received, understood and responded to propotionally. The response of each study program element to student mental health issues varies, such as providing psychological services for those who need them, creating social media content, holding seminars and webinars. Regarding the scheme for handling mental health issues by mapping the problems and human resources skilled in counseling. In particular, there was formed peer counselors, all lecturer were directed to act as professional psychologists, utilize and teach human resources to do counseling properly, and provide information flow to offer psychology services in faculty, so students would access the latest mental health information easily.